RITUXIMAB IN THE TREATMENT OF REFRACTORY IDIOPATHIC MEMBRANOUS NEPHROPATHY IN PAKISTANI POPULATION - Anjum, Nosheen; Nabi, Zahid; Alam, Muhammad Adeel (Journal of Ayub Medical College Abbottabad, 2019)
This is the time of paradigm shift in the treatment of primary membranous nephropathy which carries a major position in causing nephrotic syndrome in adult population and has been labelled as a cause of idiopathic primary glomerulonephropathy in about 90% of patients. It is two folds more common in male population as compared to female population.It is held responsible for about 0.7% cases of end stage kidney disease. However, unfortunately, the optimal treatment for idiopathic membranous nephropathy is still unresolved. Rituximab has been made specially to attach to CD20 receptors and therefore cause depletion of B cells.It has been found to be a potential treatment option for idiopathic membranous nephropathy. We present four cases of primary idiopathic membranous nephropathy that were successfully treated with rituximab. They were all previously treated with conservative management followed by immunosuppression therapies but none of them was fortunate enough to achieve partial or complete remission. Therefore, all of them were given two doses of rituximab (375 mg/m2), two weeks apart. Except for only one of the patients who required a second round of rituximab therapy, they all achieved complete remission of the disease without any significant side effects of the drug. This represents that those patients of idiopathic membranous nephropathy who are refractory cases with use of steroids, calcineurin inhibitors, (cyclosporine or tacrolimus) or alkylating agents (cyclophosphamide or chlorambucil) still have a hope in the form of Rituximab which has no doubt shown promising results in Pakistani population. Indeed, Rituximab may also be used early in the course of the disease to improve the outcome of the disease. Keywords: primary idiopathic membranous nephropathy; Proteinuria; Rituximab; Cyclophosphamide; Cyclosporine; Tacrolimus; Corticosteroids; nephrotic syndrome